2014
DOI: 10.1073/pnas.1413118111
|View full text |Cite
|
Sign up to set email alerts
|

Global structural changes of an ion channel during its gating are followed by ion mobility mass spectrometry

Abstract: Mechanosensitive ion channels are sensors probing membrane tension in all species; despite their importance and vital role in many cell functions, their gating mechanism remains to be elucidated. Here, we determined the conditions for releasing intact mechanosensitive channel of large conductance (MscL) proteins from their detergents in the gas phase using native ion mobilitymass spectrometry (IM-MS). By using IM-MS, we could detect the native mass of MscL from Escherichia coli, determine various global struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 61 publications
4
90
0
Order By: Relevance
“…This model was verified and revised by further studies through electron paramagnetic resonance spectroscopy (24) and an electrostatic repulsion test (25). More recently, a study through the native ion mobility-mass spectrometry demonstrated that MscL has the inherent structural flexibility to achieve large global structural changes in the absence of a lipid bilayer (26).…”
Section: Significancementioning
confidence: 86%
“…This model was verified and revised by further studies through electron paramagnetic resonance spectroscopy (24) and an electrostatic repulsion test (25). More recently, a study through the native ion mobility-mass spectrometry demonstrated that MscL has the inherent structural flexibility to achieve large global structural changes in the absence of a lipid bilayer (26).…”
Section: Significancementioning
confidence: 86%
“…Recently there has been an upsurge in the use of other non-ionic detergents for native MS analysis of MPs, for example, Triton X-100, tetraethylene glycol monooctyl ether (C8E4), octaethylene glycol monododecyl ether (C12E8), lauryldimethylamine N-oxide (LDAO), and n-octyl-b-D-glucoside (b-OG) (Fig. 4) as it has been shown that these detergent micelles dissociate at much lower activation energies, often resulting in MP ions that are more native-like [95][96][97]. These detergent micelles may be dissociated more easily than those formed by DDM as their non-ionic nature means that the only stabilizing forces are hydrophobic interactions which are weakened in the gas-phase, whilst DDM and b-OG micelles are also stabilized by hydrogenbonding [95].…”
Section: Detergent-based Reconstitution Methods For Native Msmentioning
confidence: 99%
“…4) as it has been shown that these detergent micelles dissociate at much lower activation energies, often resulting in MP ions that are more native-like [95][96][97]. These detergent micelles may be dissociated more easily than those formed by DDM as their non-ionic nature means that the only stabilizing forces are hydrophobic interactions which are weakened in the gas-phase, whilst DDM and b-OG micelles are also stabilized by hydrogenbonding [95]. It has also been proposed that the relative ease of detergent removal may relate to the stability of the protein within Fig.…”
Section: Detergent-based Reconstitution Methods For Native Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, an improved open E. coli MscL (EcMscL) 3D structure was determined using both ensemble and single molecule site-directed fluorofore labelling (SDFL) FRET spectroscopy in combination with MD simulations 6,10,11 in agreement with the X-ray structure of an expanded form of an archaeal MscL homolog from Methanosarcina acetivorans 12 . While the overall gating-related structural changes in MscL have largely been established 8,11,13,14 the structural dynamics and physiological role of the C-terminal domain has thus far been controversial. Several studies have suggested that the C-terminus should remain intact during gating and could function as a molecular sieve 15,16 , while others suggested that this helical bundle should actively participate in gating and that opening of the MscL channel was accompanied by complete dissociation of the bundle 13,17 .…”
mentioning
confidence: 99%